Enhanced photocatalytic activity of TiO2–Cu/C with regulation and matching of energy levels by carbon and copper for photoreduction of CO2 into CH4. Issue 16 (5th April 2016) - Yan, Yabin; Yu, Yanlong; Cao, Chi; Huang, Shaolong; Yang, Yajun; Yang, Xiaodan; Cao, Yaan
Abstract : A novel copper and carbon co-modified TiO2 photocatalyst (TiO2 –Cu/C) was prepared using a simple sol–gel method. Abstract : A novel copper and carbon co-modified TiO2 photocatalyst (TiO2 –Cu/C) was prepared using a simple sol–gel method. The properties of the photocatalysts were investigated by XRD, Raman, BET, HRTEM, EDAX, XPS, absorption spectroscopy and PL techniques. It was revealed that copper was present as –O–Cu–O– species and carbon existed as elementary substance carbon nanoparticles on the surface of TiO2 . Based on the experimental results, the band structure and electronic density of states of TiO2, TiO2 –Cu and elementary substance carbon are predicted by theoretical calculations. The energy levels of the –O–Cu–O– species and the carbon nanoparticles were located above the valence band, which extends the absorption into the visible light region, facilitate the separation of photogenerated charge carriers and provide hole reactive sites on the surface. Thus, the photocatalytic activity of TiO2 –Cu/C is much higher than that of pure TiO2, TiO2 /C and TiO2 –Cu for photoreduction of CO2 and H2 O into CH4 under UV-light irradiation.